Сучасні аспекти розвитку системи оподаткування туристичної індустрії в національній економіці України - Гальцова, О.Л.; Galtsova, Olga; Юрченко, Наталія Іванівна; Yurchenko, Nataliia (Класичний приватний університет, 2019)
У статті охарактеризовано актуальні проблеми розвитку системи оподаткування туристичної індустрії в національній економіці України, де туристична діяльність має особливості щодо оподаткування основними податками і зборами. Це зумовлено особливим характером операцій із надання туристичних послуг, які передбачають широке використання посередницьких схем, та наявністю спеціальних норм. Розглянуто правила формування податкового кредиту. Проблемою є розрахунок бази оподаткування, коли туроператор реалізує свої послуги через туристичних агентів, оскільки діючи норми роблять неможливим зменшення бази оподаткування на суму винагороди турагента, оскільки такі послуги не входять до вартості туристичного продукту. З метою оподаткування необхідно відображати окреме отримання посередницьких послуг від турагента, на основі податкових накладних турагента нараховувати податковий кредит. Визначено базу оподаткування ПДВ, правила формування податкового кредиту, а також особливість його обліку. Розмір стягнутого податку може бути не дуже великим, але матиме негативний вплив на сектор туризму, який призведе до негативних наслідків для всієї економіки; це стосується тих податків, які накладені безпосередньо на туристів. Відвідуванню країни можуть перешкоджати високі ставки. Розрахунки між туристами та суб’єктами господарської діяльності, які надають туристичні послуги, що здійснюються через посередників, утворюють туристичний продукт, який створює складності в оподаткуванні. Тому внесення змін до Податкового кодексу в частині оподаткування турагентів є необхідним для забезпечення позитивних тенденцій розвитку туристичного бізнесу в Україні. The article describes the actual problems of the taxation system of the tourism industry of Ukraine. Tourist activity in Ukraine has specific features regarding taxation of basic taxes and fees. This is due to the special nature of travel services, which involve widespread use of intermediary schemes, and the existence of special rules in the value added tax Act and the Law on Profit. As a result of the research, it should be noted that certain problems in taxation of the tourism industry have a significant impact on the overall well-being of the entire country. The main source of foreign currency inflows is international tourism. Income derived from tourism taxation can be used to provide public goods, such as improving communal services. But on the other hand, tourism taxes are very high, so companies in the tourism industry, consumers of tourist services and international organizations require a reduction in taxes and a reduction in tax rates. It should be noted that the deterioration in the level of protection of consumers’ rights in the tourist market is the possibility of adopting the Tax Code of Ukraine. The problematic aspects of the Code relating to the value added tax taxation of tour operator and travel agents compel to reconsider the contractual relations of the tour operator and the travel agent who do not comply with the legislation in the tourism industry regarding the mediation status of the travel agent. When conducting operations to supply a tourism product to a tourist product intended for its consumption both in the territory of Ukraine (domestic tourism) and abroad (international tourism), the tax base is the remuneration, which is defined as the difference between the value of the tourist product supplied to it and the cost of the cost incurred by such a tourist operator as a result of the creation of such a tourist product. The most important is that value added tax obligations on a tourist operator when supplying a tourist product arise at the date of registration of the document, which certifies the fact of the tourist product supply. Accordingly, on the date of receipt by the tourist operator of an advance on the tourist product, tax obligations are not formed. The feature of the value added tax registration of travel agencies is characterized by such moments as the nature of the service provided and the special procedure for increasing the tax liability, as well as tax credit related to tax accounting. Tax accounting varies depending on the type of travel services (foreign, foreign or domestic tourism). The problem is the calculation of the tax base when the tour operator implements its services through travel agents, since the operating norms make it impossible to reduce the tax base to the amount of remuneration of the travel agent, since such services are not included in the value of the tourism product. The amount of tax deducted may not be very high, but will have a negative impact on the tourism sector, which will lead to negative consequences for the whole economy. This applies to taxes that are imposed directly on tourists (payment of visas). Visits to the country can be hampered by high rates. The settlements between tourists and business entities engaged in tourism, they provide tourist services, which are carried out through intermediaries – form a tourist product that creates complexity in taxation. Changes to the Tax Code as part of the taxation of travel agents are necessary to ensure positive trends in the development of Ukrainian tourism business.
Current aspects of the development of the taxation system of the tourist industry in the national economy of Ukraine
Keywords: національна система оподаткування; national tax system; ПДВ; value added tax; туристичні агенти; travel agents; туристичні оператори; tour operators; туристичний продукт; tourist product